KESUSASTRAAN: AJARAN NILAI-NILAI MORAL MASA HAMENGKUBUWONO V - Gandes Sekar Putri (Universitas Negeri Yogyakarta, 2017)
ABSTRACT The study of the values of leadership of Hamengkubuwono V can be found in the literary works that developed at that time. The literary work of Hemangkubuwono V period is growing rapidly and contains moral teachings that can be the reference of today. One of the emerging literary works, namely Serat Jatipusaka Makutharaja which exemplifies a leader in acting, values leadership as exemplary form and values of leadership that are implemented in life. The study of the value of leadership on literary works in this paper can be referred to as the Javanese-Islamic leadership model. Keywords: literary works, moral values, Hamengkubuwono V